Triethylenetetramine-modified ammonium polyphosphate as charring agent for enhanced flame retardancy in ethylene vinyl acetate copolymer - Yi-Song Wang; Wen Ye; Yan Jiang; De-Yi Wang (Advanced Industrial and Engineering Polymer Research)
In this study, a novel charring agent (TETA-APP) was prepared via ion exchange reaction between triethylenetetramine (TETA) and ammonium polyphosphate (APP). It was characterized by fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy analysis (SEM), X-ray photoelectron analysis (XPS), and X-ray diffraction analysis (XRD), etc. Furthermore, the obtained TETA-APP was blended with APP to act as flame retardant in ethylene vinyl acetate copolymer (EVA), and the comprehensive properties of the composites were tested. Compared with IFR@EVA-1 (30 wt% APP in EVA), IFR@EVA-3 with 15 wt% TETA-APP and 15 wt% APP in EVA resin resulting in 32.1 % of limiting oxygen index (LOI) and V-0 grade of vertical burning test (UL-94), and showed a significant decrease in both the values of pHRR (reduced by 54.5 %) and SPR (reduced by 46.0 %) in cone calorimetric (CC) analysis. These results demonstrated that TETA-APP performed obviously synergistic effect in APP/EVA system. Then thermogravimetric-infrared spectroscopy (TG-FTIR) and Raman spectroscopy were used to further investigate the flame-retardant mechanism. In gaseous phase, the degraded CO2, NH3 and H2O acted as diluents reducing oxygen density, and the formed PO· performed quenching effect to capture free radicals. In condensed phase, a large number of -P-N-C-, -P-C- bonds produced by the decomposition of TETA-APP were helpful for forming a more stable char layer, which restricted the exchange of heat and flammable pyrolysates. Both the effects in gaseous and condensed phases were the principal reason for the much better flame retardancy in EVA resin.